O autor que não era visível para quem estava na estrada - Souza Júnior, Luís Roberto de (2020)
This thesis is linked to the area of concentration in Creative Writing and, therefore, is divided into main two sections: one of fiction and one of essays. The fictional section consists of a short stories' book, a novella and a collection of poems. In these texts, the objective was to investigate, through the practice of writing, the compositional possibilities of each genre. The essay section assumes that, even in countries with more tradition than Brazil in the Creative Writing, there is a permanent state of elaboration and questioning regarding the area’s multiple aspects. In Brazil, where the area is relatively new, it is necessary, above all, to increase the body of knowledge in relation to it. To this end, the essays problematize points such as the role of the area within the literary system, the meaning of the term Creative Writing, its history, the teaching and learning process.